Stoichiometric Effects of Feed Ratio on Syngas Production from CO2 Reforming of Methane over SmCoO3 Perovskite Catalyst - Osazuwa, Osarieme U.; Cheng, C. K. (Dept. of Chemistry, UTM, 2017)
An effective way of consuming the two most dominant gases (CO2 and CH4) which are heavily linked with heat waves across the globe is the CO2 reforming of methane reaction. This study describes the use of sol-gel citrate method to prepare SmCoO3 perovskite catalyst and thereafter, catalytic test was carried out on the methane reforming reaction platform to produce syngas. The physicochemical properties of SmCoO3 perovskite catalyst were determined pre-activity evaluation by TGA, N2 physisorption, EDX, XRD, and post-activity evaluation by EDX and TGA. Results from the pre-reaction characterization showed the formation of crystalline and monophasic perovskite structure, while the post-reaction characterization showed evidence of carbon species associated with methane reforming reactions. The catalytic reaction was performed at atmospheric pressure on a reactor bed using a gas hourly space velocity of 30,000 h-1 and the activity was studied at stoichiometry (CO2: CH4 1:1), below (CO2: CH4 1:2) and above stoichiometry (CO2: CH4 2:1) of reactant gas at reaction temperature of 1023 K. Results showed highest CO2 and CH4 conversion of 85% and 84% respectively and optimum syngas yield (H2: CO) of 60% and 57% respectively at stoichiometry ratio.